From Jurisprudence to Algorithms: The Role of Artificial Intelligence in Contemporary Sharia Financial Decision-Making - Edi Mulyono; Mahmoud Mohamed Ali Mahmoud Edris (Nusantara: Journal of Law Studies, 2025)
The development of Artificial Intelligence (AI) has had a profound impact on the modern financial system, including the Islamic finance sector. Today, AI is utilized to support risk analysis, financing decision-making, and the management of Sharia-based investment portfolios. However, the application of AI in Islamic finance also raises several legal and ethical issues that require in-depth examination from the perspective of contemporary fiqh muamalah. This study aims to analyze the compatibility of AI implementation in Islamic financial decision-making with the principles of maqāṣid al-syarī‘ah, justice, and human responsibility (taklīf). This research employs a qualitative method with a normative-theological approach and descriptive-analytical analysis. Primary data were obtained from the study of fatwas, regulations, and practices of Islamic financial institutions that have adopted AI, while secondary data were derived from academic literature, scholarly journals, and contemporary Islamic legal writings. The analysis was conducted through the stages of reduction, classification, and normative interpretation to assess the harmony between Sharia principles and technological innovation. The findings suggest that the application of AI in Islamic finance is permissible as long as it does not contravene the principles of honesty and justice, and continues to prioritize humans as moral supervisors and legal subjects. Academically, this study enriches contemporary fiqh muamalah discourse by providing a normative framework for developing AI-related regulations and ethics that align with the maqāṣid al-sharī'ah. It also encourages an interdisciplinary dialogue between Islamic law, technology ethics, and the digital economy toward an adaptive and sustainable Sharia financial system.